Michael Angelo - Cooper, Allan Elizabeth (My University, 1907)
Introduction: Most of our information concerning Michael Angelo has come through the biographies of him written by Condivi and Vasari. The most complete history of Michael Angelo, and his age, is that which was written by Herman Grimm the material being gathered from Condivi’s and Vasari’s biographies, Michael Angelo’s letters and a very careful and complete study of his works. -- previous to Michael Angelo’s birth, his father, Ludovico, received an appointment as Governor of the little fortified cities of Chiusi and Caprese situated on the , where he and his wife immediately repaired. Here on the 6th of March 1475. The child was born who received the name of Michael Angelo. This being the true orthography instead of the more usual one of Angelo. Two years later when his term expired Ludovico and his wife returned to Florence leaving the little Michael Angelo with the nurse on the Buonarroti estate, three miles outside of Florence. In these surroundings, he began to draw as soon as he could use his hands. His brothers were merchants and this being a more esteemed profession than painting, his uncle and father tried in every way to prevent him from becoming an artist, even resorting to punishment. However, they found it impossible to overcome his love for art so in April, 1488 his father signed a contract, by nature of which, he was articled to the masters Domenico and David Ghirlandaio for three years. He made rapid progress here and it soon became evident that he had surpassed his masters, in the knowledge of his art. It seemed imperative that he sever his connection with Ghirlandaio before the expiration of the three years and this was accomplished by his acquaintance with Lorenzo de’ Medici who was at the head of the government at Florence.
Citation: Cooper, Allan Elizabeth. Michael Angelo. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Michael Angelo; The Renaissance; Fifteenth Century History; Italian History; Theses; Manuscripts (documents)